The Effectiveness of Mindfulness Skills Training on Improving Extramarital Relationships by Emphasizing the Mediating Role of Emotional Schemas - Zahra Nikbakht; Ali Farnam; Farhad Kahrazehi (Iranian Evolutionary Educational Psychology Journal)
Objective: This study aimed to evaluate the effectiveness of mindfulness skills training on improving extramarital relationships by emphasizing the mediating role of emotional schemas in married students of Zahedan universities. Methods: The research method in this research was quasi-experimental, and the data collection tool was two standard questionnaires, Glass (1988) and Leahy (2000). The data analysis tools in this study were SPSS and AMOS statistical software. Due to the method and nature of the hypotheses of this study, the combined covariance test with repeated measures (GLMRM) was used for the effectiveness of the mindfulness skills, and regression models with hidden variable were used to evaluate the mediation effect of emotional schemas. The statistical population of this study includes married students of Zahedan universities in 2019-2020. The sample size in this study was forty people who were divided into two groups (one control and one experimental group of twenty people). The sampling method was simple random sampling. Results: According to the results of this study, with a 95% confidence level (p<0.05), mindfulness skills training is effective in improving extramarital relationships and emotional schemas, and emotional schemas have a minor mediating role in the relationship between mindfulness skills and extramarital relationships. Conclusion: The findings aid family psychologists in effectively addressing the challenges presented by extramarital relationships within couples.